2016
DOI: 10.3832/ifor1773-009
|View full text |Cite
|
Sign up to set email alerts
|

Different harvest intensity and soil CO2 efflux in sessile oak coppice forests

Abstract: Soil CO2 efflux accounts for about 45-80% of total ecosystem respiration and is therefore an important part of the ecosystem carbon cycle. Soil CO2 efflux has been poorly studied in forests managed in the ancient coppicing manner. In our study, soil CO2 efflux, temperature, and moisture were measured in sessile oak stands with different harvesting intensity (control: 0% intensity; V1: 75%; V2: 80 %; V3: 85%; and V4: 100%) during the fifth and sixth years after harvesting. Soil CO2 efflux was in the range 2-8 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 41 publications
(57 reference statements)
5
5
0
Order By: Relevance
“…3), so it is variable in time. We also observed that harvest increased soil water content, and that is consistent with other studies (Londo et al 1999;Čater and Simončič 2010;Darenova et al 2016). The largest differences in SWC between control and harvested plots were observed during the first half of the first season after harvest.…”
Section: Discussionsupporting
confidence: 92%
“…3), so it is variable in time. We also observed that harvest increased soil water content, and that is consistent with other studies (Londo et al 1999;Čater and Simončič 2010;Darenova et al 2016). The largest differences in SWC between control and harvested plots were observed during the first half of the first season after harvest.…”
Section: Discussionsupporting
confidence: 92%
“…Q 10 in the mature forest was the lowest compared to the coppiced stands. This finding is consistent with the previous study of Darenova et al (2016) who observed lower Q 10 in a high forest than in a coppice, which was sparser than on our experimental plots. From this result we can speculate, that in mature forest soil CO 2 efflux there is a higher proportion of root respiration Table 3.…”
Section: Temporal Dynamics Of R Ssupporting
confidence: 94%
“…R 2 of these relationships was always higher than 0.80, which confirms that soil temperature was a driving factor of temporal dynamics of R S at this site during periods without soil water limitation. The parameter of temperature sensitivity of R S (Q 10 ) ranged between 1.85 and 2.56 among the plots, which is comparable to recent findings for oak forests (Darenova et al 2016;Luan et al 2011;Rey et al 2002). Q 10 in the mature forest was the lowest compared to the coppiced stands.…”
Section: Temporal Dynamics Of R Ssupporting
confidence: 86%
See 1 more Smart Citation
“…Within the forest stand close to the experimental plots, the continuous measurements of soil CO2 efflux were carried out applying an automated closed (non-steadystate through-flow) system (developed at the Global Change Research Institute in Brno, CZ) with six chambers. The design and installation were described by Darenova et al (2016). Within each chamber, the soil temperature (thermometers PT-100 ® , Treston a.s., CZ) was measured simultaneously with soil CO2 efflux at the depth of 1.5 cm.…”
Section: Measurement Of Soil Co 2 Efflux In Situ and Expression Of R 10mentioning
confidence: 99%